Four stories for four seasons - De Paola, Tomie (New York : Half Moon Books, 1977)
Four friends, a cat, dog, pig, and frog, share the delights of each season.
3.0
K-3
K-3
Book Links (A.L.A.)
Keywords: Seasons -- Fiction; Friendship -- Fiction; Animals -- Fiction; Seasons -- Fiction; Friendship -- Fiction; Animals -- Fiction